2011
DOI: 10.1093/ndt/gfr664
|View full text |Cite
|
Sign up to set email alerts
|

IgA nephropathy recurs early in the graft when assessed by protocol biopsy

Abstract: IgAN recurrence rate was 32%. The histological diagnosis was not accompanied by abnormalities in the urinalysis in one-half of the patients. Full DR match and cyclosporine were associated with non-recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
63
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 29 publications
2
63
1
Order By: Relevance
“…The reported frequency of histological or clinically significant recurrence of IgAN varies from 13% to 60% . This large variation showed in the reported literature is attributed to the differences in the duration of follow‐up and in the biopsy policy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported frequency of histological or clinically significant recurrence of IgAN varies from 13% to 60% . This large variation showed in the reported literature is attributed to the differences in the duration of follow‐up and in the biopsy policy.…”
Section: Discussionmentioning
confidence: 99%
“…Longer follow‐ups have higher probabilities to find recurrent IgAN than shorter ones, and the frequency of histological recurrence of IgAN increases when protocol biopsy is performed because histological recurrence without evidence of clinical manifestation is common. Ortiz et al . reported that 52% of the IgAN recurrences diagnosed by protocol biopsies were not accompanied by proteinuria or haematuria.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplantation is one of the therapeutic options offered to these patients; however, recurrence of IgAN on the graft can occur with a frequency ranging from 20 to 60%. [1][2][3][4] The immunosuppressive regimen seems to affect the recurrence rate, with antithymocyte globulin reportedly associated with a decrease in recurrence frequency, 5 whereas withdrawal of steroids is associated with an increased risk. 6 However, there is no specific treatment for recurrent IgAN.…”
mentioning
confidence: 99%
“…[6] Importantly, it was found that 52% of the IgAN recurrences diagnosed by protocol biopsies were not accompanied by proteinuria or hematuria. Thus, protocol biopsies with immunofluorescence analysis constitute an essential tool for the diagnosis of recurrence, even if it is clinically silent [7]. In our study, we were not able to rule out the possibility that IgA deposits were already present in the donors.…”
Section: Discussionmentioning
confidence: 65%